"Clinton defeats Trump" 2016 polls and the shadow of 1948. Issue 4 (2nd August 2017) - Lusinchi, Dominic
Abstract : Dominic Lusinchi finds parallels with the past while reviewing a report on last year's presidential election polls Abstract : Dominic Lusinchi finds parallels with the past while reviewing a report on last year's presidential election polls.